Chemical composition, antimicrobial activity and antiviral activity of essential oil of Carum copticum from Iran - Reza Kazemi Oskuee; Javad Behravan; Mohammad Ramezani (Mashhad University of Medical Sciences, 2011)
Objectives: Evaluation of therapeutic effects of Carum copticum (C. copticum) has been the subject of several studies in recent years. Thymol the major component of C. copticum is a widely known anti-microbial agent. In this study, the antibacterial and anti viral activities of essential oil of C. copticum fruit were determined. Materials and Methods: Essential oil of C. copticum was analyzed by means of gas chromatography-mass spectrometry (GC-MS). The antimicrobial activity of the oil was evaluated against six Gram (+/-) bacteria and fungi, using the micro broth dilution technique. Antiviral activity of the essential oil was evaluated using a Bacillus phage CP51. Results: From the ten identified constituents, representing 98.7% of the oil, thymol (72.3%), terpinolene (13.12%) and o-cymene (11.97%) were the major components. It was found that the oil exhibited strong antimicrobial activity againstStaphylococcus aureus (S. aureus) andBacillus subtilis (B. subtilis) (MIC, 0.00025% v/v). Furthermore, the antiviral activity of the oil was evaluated by plaque reduction assay. Conclusion: The essential oil showed an antiviral activity against phage when phage was pre-incubated with the essential oil prior to its exposure to B. cereus and without any pre-incubation with the phage, suggesting that the oil directly inactivated virus particles.